THE EXPERIENCE OF PREGNANCY IN ADOLESCENCE ON FAMILY AND SOCIAL SCOPE - Carolina Carbonell dos Santos; Laís Antunes Wilhelm; Camila Neumaier Alves; Luiza Cremonese; Crislen Malavolta Castiglioni; Larissa Venturini; Carolina Frescura Junges; Lúcia Beatriz Ressel (Revista de Enfermagem da Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976929860